Analisis Pemberian Teknik Deep Massage terhadap Penurunan Nyeri pada Ibu Bersalin Kala 1 Fase Aktif - Septi Fitras Ningtyas; Mudhawaroh Mudhawaroh (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2022)
Deep back massage is one of the pain management methods in the form of massage where the sacral area is pressed firmly with the palm of the hand, released, and pressed back. The patient lies down and is performed for 20 minutes during the contraction. (± 6 contractions). The purpose of this study was to determine the effect of deep back massage on the first stage of labor in the active phase of primigravida inpartu mothers. The type of research used is pre-test pre-test control group design and post-test test design of experiment. The sample size was 26 using the sample allocation method and divided into two groups: 13 in the intervention group and 13 in the control group. This study was conducted by observing active labor in phase I in partum primigravida mothers from October 1 to November 31, 2018. The analytical test used was the Wilcoxon matched pair test. Based on the results of the Wilcoxon match pair test, the z count value was 2.179 and a significant difference was 0.029 & lt;. 0.05. From this it can be concluded that deep back massage in the first stage of the active phase of primigravida in partu women affects work. Proper and frequent deep back massage by the obstetrician and family reduces labor pains in the early stages of activity.